EFFECT OF YOGA TRAINING ON FLEXIBILITY AND BALANCE AMONG JUMPERS: AN EXPERIMENTAL STUDY (International Journal of Food and Nutritional Sciences, 2023)
This study investigated the effect of a 12-week yoga intervention on flexibility and balance among jumpers from Adikavi Nannaya University. A total of 20 participants were divided into an intervention group (n=10), which underwent yoga training, and a control group (n=10), which received no intervention. Pre- and post-test measurements of flexibility and balance were conducted, and data were analyzed using paired sample t-tests and ANCOVA. The results indicated a significant improvement (p < .001) in flexibility and balance within the intervention group, while no substantial changes were observed in the control group. The improvements in the intervention group can be attributed to neuromuscular adaptations, proprioceptive enhancement, and increased muscle elasticity facilitated by yoga practice. These findings suggest that yoga can be an effective supplementary training method for athletes, particularly those requiring enhanced mobility and postural stability. It is recommended that yoga be integrated into sports training regimens to optimize movement efficiency, reduce injury risk, and improve performance. Future research should explore longer intervention periods, combined training approaches, and biomechanical analyses to further understand yoga’s impact on athletic performance.